A lot to a little or a little to a lot—which dose-volume relationship ensures the best clinical outcome in the high dose radiation therapy of thoracic tumors? A prospective approach - Schröder, Christina; Engenhart-Cabillic, Rita; Vorwerk, Hilke; Schmidt, Michael; Huhnt, Winfried; Blank, Eyck; Sidow, Dietrich; Buchali, André (Journal of Thoracic Disease, 2016)
Background: The purpose of this prospective randomized trial is to determine which constellation of dose and corresponding volume of the lung tissue—either a lot to a little or a little to a lot—should be preferred to ensure the best possible outcome for patients with thoracic carcinomas. Methods: From Apr 2012 to Oct 2015, 81 patients with NSCLC, SCLC or esophageal carcinoma were randomized and treated with either a 4-field-IMRT or a VMAT technique with or without additional chemotherapy. Data regarding clinical outcome, pulmonary function tests (PFT) and quality of life (QoL) was collected before RT, 6 weeks, 12 weeks and 6 months after treatment, QoL data additionally 1 year post RT. Follow up CTs were done 12 weeks and 6 months after RT. Results: There is no significant difference regarding the local (P=0.954) and distant (P=0.206) outcome, side effects (all P>0.05) or survival (P=0.633) at any follow-up appointment. The comparison of the PFT shows a statistically significant difference for the DLCO 6 weeks post RT (P=0.028). All other parameters do not differ significantly at any follow up appointment. Regarding the QoL there is no statistically significant difference at any follow up appointment (P>0.1). There is a statistically significant difference between the mean density of the lung parenchyma at 12 weeks (P